A turn on fluorescent probe for Zn2+ based on Quinoline with flexible chelating group - Dacheng Zheng; Rui Huang; Haichuang Lan (Results in Chemistry)
In this work, a Zn2+ fluorescent probe based on quinoline was designed and synthesized. The flexible diethanolamine was attached to 8-Hydroxyquinoline-2-carboxaldehyde, forming a well-dissolved and biocompatible fluorescent probe. As a recognition group, the diethanolamine not only maintained selectivity for zinc ions, but also had good anti-interference ability to pH. The synthesis process of the probe (QE) was described in detail and characterized by 1H, 13C and HRMS. The sensing performance (pH stability, response time, and detection limit) of the probe for zinc ions in buffer solution PBS and live human gingival fibroblasts was extensively investigated. This pH-resistant probe provided a powerful tool for studying the synergistic effect of drugs and zinc ions.